Search, Solve, Create, and Share (SSCS) Learning Model: The Impact on the Students Creative Problem-Solving Ability on the Concept of Substance Pressure - Rahma Diani; Hesti Herliantari; Irwandani Irwandani; Antomi Saregar; Rofiqul Umam (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
This study aimed to determine the effectiveness of the Search, Solve, Create, and Share (SSCS) learning model and its impact on the students creative problem-solving ability. The study was conducted on eighth-grade students of Junior High School 24 (SMPN 24) Bandar Lampung, Indonesia, on the Substances Pressure subject matter. This is quasi-experimental with non-equivalent control group design. The independent sample t-test showed that the SSCS model influences the students creative problem-solving ability, of which the experimental class is higher than the control class. Furthermore, the results of the effect size obtained the d value of 2.39, indicating the SSCS learning model is effective for the students' creative problem-solving ability which belongs to the high category.